2021
DOI: 10.4103/ijri.ijri_567_20
|View full text |Cite
|
Sign up to set email alerts
|

Perception and practice regarding infection control measures in Radiology department during pre-COVID and COVID times—A survey among radiologists and a review of current concepts and literature

Abstract: Aim: In this study, we aim to evaluate the perception and practice of IPC measures by Radiologists during pre-COVID and present COVID times, while conducting a thorough review of current concepts and literature, to provide a standard operating procedure (SOP) for radiology operations. Methods: This study was conducted by Department of Radiodiagnosis and Imaging, Kasturba Medical College, MAHE, Mangalore. After obtaining approval from the institutional ethics committee, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 12 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…2 . There were three main types of literature included: eleven incident report reviews or case studies [ 20 30 ], five literature reviews [ 2 , 31 – 34 ], and thirty articles that employed data collection or clinical evaluations [ 35 64 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2 . There were three main types of literature included: eleven incident report reviews or case studies [ 20 30 ], five literature reviews [ 2 , 31 – 34 ], and thirty articles that employed data collection or clinical evaluations [ 35 64 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The most reported geographic location of the MID where data collection occurred (rather than authors’ affiliation) was Germany ( n = 6). The type of data collection methods used most commonly were surveys/questionnaires [ 42 , 43 , 48 – 51 , 53 55 , 57 – 64 ], followed by microbial analysis [ 35 , 37 – 44 , 46 , 47 , 52 , 54 , 56 ], simulation studies [ 35 , 36 , 38 , 52 ], direct observation or review of practice [ 44 , 49 , 51 ], timing [ 41 , 43 ], and animal studies [ 45 ], as described in Table 3 . The number of citing texts including each of the five SEIPS domains for studies that included data collection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations